2021
DOI: 10.2478/lpts-2021-0024
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Gas as a Sustainable Fuel Atlernative in Latvia

Abstract: Despite various benefits that the natural gas mobility can provide, CNG (hereinafter – compressed natural gas) and LNG (hereinafter – liquified natural gas) filling infrastructure both in Latvia and the Baltic States as a whole is still at the stage of active development. As a result, the natural gas fuelled vehicle fleet comprises less than 1 % of all registered road vehicles in the Baltics, but, with regards to transport and climate policies of the European Union (hereinafter – the EU), it has a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Jobbágy (2013) [26] found that the payback of new CNG-powered light-duty vehicles (Opel Zafira 1.6 CNG Turbo Essentia 150 HP and Volkswagen Touran 1.4 TSI EcoFuel Trendline 150 HP) in Hungarian road conditions could be 2 to 7 years. Savickis et al, (2021) [27] revealed that the light-duty vehicle-SEAT LEON 1.5 TGI MAN-6 fueled by CNG-could start to pay off at 57,650 km as an alternative to petrol. For the diesel trucks with dual fuel, the maximum PB d and PB p are 29,304 km and 2.5 months, respectively.…”
Section: Economic Assessment Of Ngvsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jobbágy (2013) [26] found that the payback of new CNG-powered light-duty vehicles (Opel Zafira 1.6 CNG Turbo Essentia 150 HP and Volkswagen Touran 1.4 TSI EcoFuel Trendline 150 HP) in Hungarian road conditions could be 2 to 7 years. Savickis et al, (2021) [27] revealed that the light-duty vehicle-SEAT LEON 1.5 TGI MAN-6 fueled by CNG-could start to pay off at 57,650 km as an alternative to petrol. For the diesel trucks with dual fuel, the maximum PB d and PB p are 29,304 km and 2.5 months, respectively.…”
Section: Economic Assessment Of Ngvsmentioning
confidence: 99%
“…Additionally, the medium-duty dual fuel NGV pays off at 7 months. Savickis et al, (2021) [27] found that SEAT LEON 1.5 TGI MAN-6 fueled by CNG pays off at 71,531 km as an alternative to diesel.…”
Section: Economic Assessment Of Ngvsmentioning
confidence: 99%
“…Namely, the usage of natural gas could increase and penetrate brand new sectors of the national economies. There is a large potential for LNG to be used as truck fuel -a cleaner alternative comparing to diesel [4].…”
Section: Source: Eurostatmentioning
confidence: 99%
“…Any LNG can be used in several crucial sectors of the national economy in order to provide reliable and clean energy: for example, it can help imeet energy needs of freight and maritime transport sectors and provide environmentally sound and affordable fuel for electric energy and heat generation [4]. Especially, in regions where renewable energy sources are less available or cannot meet high energy demand in winter season [5]- [7].…”
Section: Introductionmentioning
confidence: 99%
“…"The Natural Gas as a Sustainable Fuel Alternative in Latvia" by J. Savickis, A. Ansone, L. Zemite, I. Bode, L. Jansons, N. Zeltins, A. Koposovs, L. Vempere and E. Dzelzitis [12] states that compressed natural gas and biomethane as well as liquid natural gas may be more suitable alternatives to conventional fuels for the decarbonisation of the transport sector in cities and other densely populated areas. On the basis of this mobility implementation experience in other European countries, the article provides an analytical insight into three basic development strategies of mobility in Latvia in this decade, with a particular focus on the prospects of simultaneous use of natural gas and biomethane as sources of compressed and liquid natural gas.…”
Section: Heat-pump Optimization Strategies For Participation In Price-controlled Demand Response In Latvian Electricitymentioning
confidence: 99%